Inequality and poverty intensity as drivers of deprivation in Eastern Indonesia - Aji Priambodo (Nur Science Institute, 2025)
Poverty in Eastern Indonesia remains a persistent challenge that continues to hinder regional development. This study examines the influence of income inequality and poverty depth on the proportion of poor people across sixteen provinces during the 2024–2025 period. Drawing on panel data, the findings provide strong evidence that disparities in income distribution and the severity of poverty are closely linked to poverty dynamics in the region. The results indicate that an increase in the Gini Index contributes to a higher poverty rate, while a rise in the Poverty Depth Index also significantly adds to the number of poor individuals. Taken together, these factors serve as important and valid explanations for variations in poverty levels. The study highlights that poverty is not solely determined by economic growth, but is also shaped by uneven distribution of development outcomes and the vulnerability of low-income households. Therefore, effective poverty reduction strategies in Eastern Indonesia should combine policies promoting fairer income distribution with well-targeted social protection programs aimed at alleviating the burden on the most vulnerable groups.